(untitled) (Baltic Journal of Sport and Health Sciences, 2012)
Research background. A collocation is a combination of two or more words that are commonly used together in English. Collocation is an indispensable element of any English text and no piece of natural spoken or written language is totally free of collocation. There exist different approaches to the concept of collocations in English. However, there is no exhaustive and uniform definition or categorization of it. Second language learners do not have many guidelines to follow considering the admissibility of collocation, thus collocations seem to be an insurmountable obstacle to the attainment of native like fluency and is one of error generating areas in general English and especially in EAP (English for Academic Purposes) and ESP (English for Special Purposes). Research aims were to analyze and systemize different theoretical approaches to the concept of collocation in English with reference to the data of scientific research as well as give the answer why collocations should be learned and taught at all levels of language proficiency and within different registers. Research method used – theoretical analysis of classical and modern research articles on collocation in English. Research results. Various linguistic schools have had different approaches to the study of collocations. Acquisition of collocations can be the source of particular difficulties for L2 leaners in attaining native-level competence. Collocations should be taught from the very beginning at all levels of language proficiency . Discussion and conclusions. As a result of analysis and systemization of scientific data the following conclusions have been made: 1. Collocation is a lexical co-occurrence of lexemes. In order a lexical combination could be called a collocation it should satisfy the criterion of frequency and grammatical structure; 2. Lexis and grammar cannot be separated; 3. Lexis is inseparable from semantics. 4. Knowledge of collocations can help develop language proficiency in such areas as English for Specific Purposes (ESP) and English for Academic Purposes (EAP). Students’ motivation to learn collocations and make good use of them in their essays, research works and academic language should be increased. Keywords: collocational, co-occurrence, language acquisition, register.